Formulation and Antibacterial Activity of Citrus limon Peel Essential Oil and Eucalyptus globulus Essential Oil Combination as Gel Hand Sanitizer with The Simplex Lattice Design Method - Muhammad Fariez Kurniawan; Rika Dwiaprinia (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2021)
Citrus limon peel essential oil (CLEO) and Eucalyptus globulus essential oil (EGEO) contain active compound limonene (CLEO) and 1,8-cineole (EGEO) which can act as an antibacterial agent. This study was conducted to determine the physical properties and the inhibition zone of combination formulas of CLEO and EGEO as hand sanitizer gel against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa bacteria. The results of physical properties and antibacterial power obtained were tested by Simplex Lattice Design (SLD) method to formulate an optimal formula. The results of the physical properties showed that the formulas were in gel form, white ivory, the scent of F1 smell CLEO, the scent of F2 smell EGEO, and the scent of F3 smell the combination of CLEO and EGEO, visually homogeneous but under the microscope magnification 40x and 100x, it showed coarse grains, the values of pH were 5.07, 5.14, and 5.01, the values of spreadability were 5.81 cm, 6.12 cm, and 5.54 cm, the values of adhesion were 7.3 minutes, and 6.9 minutes, and 8.1 minutes, and the values of the viscosity were 171 dPa.s, 170 dPa.s, and 171.3 dPa.s. Antibacterial power tested by disc paper method, the results of antibacterial activity showed that the formula tested, showed that F1 100% CLEO, F2 100% EGEO, and F3 50% CLEO: 50% EGEO had antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa bacteria. The inhibition zones of each formula in a row were: inhibition zones of F1 were 9.77 mm, 11.22 mm, and 11.77 mm, inhibition zones of F2 were 10.55 mm, 12.77, and 11.88 mm, and inhibition zones of F3 were 11.66 mm, 11.55 mm, and 10.55 mm. Based on the SLD, the optimal formula of hand sanitizer gel was 20% Citrus limon essential oil and 80% Eucalyptus globulus essential oil, with the pH value was 5.50 and adhesion value was 7.20 minutes, the zones of inhibition against S. aureus, E. coli, and P. aeruginosa were 19.99 mm, 12.22 mm, and 11.44 mm